Meningkatkan Pemahaman Ibu tentang ASI Eksklusif Melalui Pendidikan Kesehatan dan Bimbingan Cara Menyimpan ASI di Wilayah Kerja Puskesmas Sukawati I Tahun 2018 - I D.A.K. Surinati (Poltekkes Kemenkes Denpasar, 2019)
Breastfeeding is one of the efforts to prevent death and malnutrition problems in infants and toddlers. According to the United Nations Children Fund (UNICEF) as many as 30,000 infant deaths in Indonesia and 10 million under-five deaths in the world each year can be prevented through exclusive breastfeeding. The purpose of community service is to increase the knowledge of mothers about exclusive education in the work area of Gianyar Sukawati I Health Center. The method used in community service is a small group discussion consisting of 3-4 people in each group targeting 50 mothers of children under five. The level of knowledge of mothers in Banjar Gelumpang Village of Sukawati before being given health education and guidance on how to store exclusive breastfeeding was largely lacking in knowledge (36%) and after that the level of knowledge of mothers became good (84%). Knowledge is the process of using senses to produce knowledge and skills. A person can know something based on the experience that has been owned, someone becomes aware of being told by someone else. Many factors that influence knowledge include educational factors, information factors are very influential on increasing knowledge because information is information, notifications, news or news about something. Health workers are expected to use the small group discussion method when providing counseling on exclusive breastfeeding.Keywords: Mother's knowledge, exclusive breastfeeding, health education.